Сучасні тенденції та основні проблеми розвитку підприємств готельного господарства в Україні - Жадан, Тетяна Андріївна; Жадан, Юлія Володимирівна; Соколова, Євгенія Борисівна (Уманський національний університет садівництва, 2022)
У статті визначено сучасні тенденції та ключові проблеми розвитку підприємств готельного господарства в Україні, які базуються на аналізі експлуатаційних характеристик та основних показників їх фінансово-господарської діяльності, що дає змогу здійснювати обґрунтований вибір найбільш ефективних інструментів антикризового управління. З’ясовано, що основними тенденціями розвитку підприємств готельного господарства в Україні є: збільшення частки готелів та аналогічних засобів розміщення у структурі колективних засобів розміщення; скорочення кількості місць, номерів, ночівль та тривалості перебування відвідувачів; низький рівень завантаженості номерного фонду; збільшення обсягів надання готельних послуг, скорочення чисельності зайнятих та витрат на оплату праці; висока питома вага збиткових готелів і подібних засобів тимчасового розміщування; прискорення процесів діджиталізації та впровадження інноваційних технологій; посилення внутрішньогалузевої конкуренції. Встановлено основні причини погіршення фінансово-економічного стану підприємств готельного господарства: загрози життю та здоров’ю людини; неоднозначність та суперечливість чинної нормативно-правової бази; несприятлива податкова політика; громіздка система бухгалтерського обліку та звітності; недосконалість системи контролю; криза неплатежів; падіння платоспроможного попиту населення; брак висококваліфікованих кадрів та ін.

The purpose of the article is to identify modern trends and key problems in the development of hotel enterprises in Ukraine. The object of the study is the process of functioning and development of hotel enterprises in Ukraine. The subject of the study is the economic activity of hotel enterprises in Ukraine. The article identified modern trends and key problems in the development of hotel enterprises in Ukraine, which are based on the analysis of operational characteristics and the main indicators of their financial and economic activity, which makes it possible to make an informed choice of the most effective anti-crisis management tools. The main trends in the development of hotel enterprises in Ukraine are an increase in the share of hotels and similar means of accommodation in the structure of collective means of accommodation; reducing the number of places, rooms, overnight stays and length of stay of visitors; low occupancy level of the number pool; increasing the volume of hotel services, reducing the number of employees and labor costs; high specific weight of unprofitable hotels and similar means of temporary accommodation; acceleration of digitization processes and introduction of innovative technologies; strengthening intra-industry competition. The main reasons for the deterioration of the financial and economic condition of hotel enterprises are threats to human life and health; the ambiguity and inconsistency of the current legal framework; unfavorable tax policy; cumbersome accounting and reporting system; imperfect control system; non-payment crisis; a drop in the solvent demand of the population; lack of highly qualified personnel, etc. The methodological basis of the research is general scientific and special methods of cognition: comparison, generalization and systematization - for the analysis of financial and economic activity of hotel enterprises in Ukraine; induction and deduction - to determine modern trends and key problems in the development of hotel enterprises in Ukraine; tabular and graphic - for visual display of research results. The information base of the research is monographs, scientific works of domestic and foreign scientists, devoted to the problems of the development of hotel enterprises; official normative documents of Ukraine; statistical materials of the State Statistics Service of Ukraine; Internet resources, etc.
Current trends and main problems of the development of hospitality enterprises in Ukraine
Keywords: підприємство; готельне господарство; суб'єкти господарювання; колективні засоби розміщення; готелі; аналогічні готелям засоби розміщення; інші засоби розміщення; enterprise; hotel industry; business entities; collective means of accommodation; hotels; similar means of accommodation to hotels; other means of accommodation